2005
DOI: 10.1091/mbc.e05-01-0067
|View full text |Cite
|
Sign up to set email alerts
|

The ATP-dependent Membrane Localization of Protein Kinase Cα Is Regulated by Ca2+ Influx and Phosphatidylinositol 4,5-Bisphosphate in Differentiated PC12 Cells

Abstract: Signal transduction through protein kinase Cs (PKCs) strongly depends on their subcellular localization. Here, we investigate the molecular determinants of PKC␣ localization by using a model system of neural growth factor (NGF)-differentiated pheochromocytoma (PC12) cells and extracellular stimulation with ATP. Strikingly, the Ca 2؉ influx, initiated by the ATP stimulation of P2X receptors, rather than the Ca 2؉ released from the intracellular stores, was the driving force behind the translocation of PKC␣ to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(61 citation statements)
references
References 36 publications
2
58
1
Order By: Relevance
“…The results presented here further demonstrate that the PKC␣ C2 CBLs, fused to another C2 domain, are sufficient for Ca 2ϩ -dependent translocation to anionic cellular membranes and phospholipid vesicles. However, although previous studies have concluded that the CBLs are responsible for exclusive plasma membrane targeting (Stahelin et al, 2003;Marin-Vicente et al, 2005), the present findings indicate that the intracellular targeting mediated by the PKC␣ C2 CBLs alone is different, and less specific, than the plasma membrane targeting of the native C2 domain. Thus, in the absence of the ␤3-4 hairpin, the CBLs target primarily to the TGN, with minor binding to the plasma membrane still detectable.…”
Section: Role Of Cbls In Targeting To Cell Membranescontrasting
confidence: 95%
See 4 more Smart Citations
“…The results presented here further demonstrate that the PKC␣ C2 CBLs, fused to another C2 domain, are sufficient for Ca 2ϩ -dependent translocation to anionic cellular membranes and phospholipid vesicles. However, although previous studies have concluded that the CBLs are responsible for exclusive plasma membrane targeting (Stahelin et al, 2003;Marin-Vicente et al, 2005), the present findings indicate that the intracellular targeting mediated by the PKC␣ C2 CBLs alone is different, and less specific, than the plasma membrane targeting of the native C2 domain. Thus, in the absence of the ␤3-4 hairpin, the CBLs target primarily to the TGN, with minor binding to the plasma membrane still detectable.…”
Section: Role Of Cbls In Targeting To Cell Membranescontrasting
confidence: 95%
“…In Vitro Association of Native PKC␣ C2 Domain with Membrane-bound PIP 2 Previous studies have implicated PS and PIP 2 as regulators of PKC␣ C2 domain docking to artificial membranes Stahelin et al, 2003;Marin-Vicente et al, 2005). As stated above, the membrane-bound target of the PLC␦ 1 PH domain, PIP 2 , is specifically enriched in the inner leaflet of the plasma membrane (Roth, 2004), whereas PS is a constituent of all cellular membranes (van Meer, 1998).…”
Section: Intracellular Targeting Of Native Pkc␣ and Its C2 Domainmentioning
confidence: 92%
See 3 more Smart Citations